The mediating role of adoption of an electronic tax system in the relationship between attitude towards electronic tax system and tax compliance - Night, Sadress; Bananuka, Juma (Universidad ESAN. ESAN Ediciones, 2020)
Purpose: The purpose of this paper is to examine the mediating effect of adoption of electronic tax system in the relationship between attitude towards electronic tax system and tax compliance using evidence fromsmall business enterprises (SBEs) of an African developing economy. Design/methodology/approach – This study used a quantitative research approach where questionnaires with close-ended questions were used. This study’s research design was cross-sectional and correlational. Usable questionnaires were received from 214 managers of SBEs and data were analysed with the help of SPSS v22 and MedGraph program (Excel version). Findings – Adoption of electronic tax system is a partial mediator in the association between attitude towards electronic tax system and tax compliance. Results further indicate that adoption of electronic taxsystemand attitude towards electronic tax system are significantly associated with tax compliance. Research limitations/implications – This study was cross-sectional and monitoring changes in behaviour over time was not possible. The study used a quantitative research approach and this limits respondents from expressing their feelings fully. The study was conducted in Uganda and it is possible that the results of this study can be generalized to developing countries with environments similar to that of Uganda.Originality/value – Whereas there has been a number of studies on tax compliance this study provides an initial empirical evidence on the mediation effect of adoption of electronic tax system in the relationshipbetween attitude towards electronic tax system and tax compliance using evidence from SBEs of an African developing economy – Uganda.

Objetivo: El propósito de este documento es examinar el efecto mediador de la adopción del sistema tributario electrónico en la relación entre la actitud hacia el sistema tributario electrónico y el cumplimiento tributario utilizando evidencia de pequeñas empresas de una economía africana en desarrollo. Diseño/metodología/enfoque - Este estudio utilizó un enfoque de investigación cuantitativa con cuestionarios de preguntas cerradas. El diseño de la investigación fue transversal y correlacional. Se recibieron cuestionarios utilizables de 214 gerentes de pequeñas empresas y los datos se analizaron con la ayuda de SPSS v22 y el programa MedGraph (versión Excel).Resultados - La adopción del sistema tributario electrónico es un mediador parcial en la asociación entre la actitud hacia el sistema tributario electrónico y el cumplimiento tributario. Los resultados indican además que la adopción del sistema tributario electrónico y la actitud hacia este están significativamente asociados con el cumplimiento tributario. Limitaciones/implicaciones de la investigación - Este estudio fue transversal y no fue posible monitorear los cambios en el comportamiento a lo largo del tiempo. Utilizó un enfoque de investigación cuantitativa y esto limita a los encuestados a expresar totalmente sus percepciones. El estudio se realizó en Uganda y es posible que los resultados puedan generalizarse a países en desarrollo con entornos similares. Originalidad/valor - Si bien se han realizado varios análisis sobre el cumplimiento tributario este estudio proporciona una evidencia empírica inicial sobre el efecto de mediación de la adopción del sistema tributario electrónico en la relación entre la actitud hacia el sistema tributario electrónico y el cumplimiento tributario utilizando evidencia de empresas pequeñas de una economía africana en desarrollo (Uganda).
Keywords: Uganda; Tax compliance; Adoption of electronic tax system; Uganda; Attitude towards electronic tax system; Cumplimiento tributario; Adopción del sistema tributario electrónico; Small business enterprises; Actitud hacia el sistema tributario electrónico; https://purl.org/pe-repo/ocde/ford#5.02.04